Kinetic study of Cr(VI) Adsorption on Hydrotalcite Mg/Al with Molar Ratio 2:1 - Puji Kurniawati, Bayu Wiyantoko, Angga Kurniawan, Tri Esti Purbaningtias (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2013)
Chromium(VI) is one of the metals that is harmful to biota and humans if large amount present in environments. One method for reducing metal contamination of Cr(VI) inaqueous is by adsorption using Mg/Al hydrotalcite with molar ratio 2:1. This study is determined the effect of contact time and adsorption models of Cr(VI) adsorption on Mg/Al hydrotalcite with molar ratio 2:1. Capacity of Cr(VI) adsorption on Mg/Al hydrotalciteoccursat the optimum contact time of 180 minutes with 93.81% percent adsorption. Adsorption kinetics model equations are analyzed with first order, second order, pseudo first order, pseudo second order, Elovich equation, the equation Dumwald-Wagner and Weber-Morris equation. Analysis model of adsorption kinetics of Cr(VI) followed pseudo second order models are characterized by the highest coefficient of determination, which is 0.998.Keywords: adsorption, Mg/Al hydrotalcite, Cr(VI), adsorption kinetic models